ANALISIS PREFERENSI GENERASI Z TERHADAP KONSEP , HARGA , DAN INOVASI DALAM KEPUTUSAN KONSUMSI PADA BISNIS KAFE DI KOTA SURABAYA - Nathania Charlene; Kristian Agung Nugraha (JURNAL ILMIAH EDUNOMIKA, 2026)
This research examines how concept, price, and innovation affect consumer purchase decisions in the café business in Surabaya. Most previous studies have primarily focused on price or product quality, with limited attention given to the combined role of concept and innovation in shaping consumer behavior. Therefore, this research positions concept and innovation as key factors that can enhance the attractiveness of products or services and ultimately influence consumer decisions. With the use of questionnaires sent out to chosen participants, this research takes a quantitative method to gathering data. The study is conducted using PLS-SEM, with the help of SmartPLS, to examine the associations between the variables. The findings demonstrate that idea, price, and innovation all play positive roles in influencing customers' purchasing decisions. However, concept is the most important aspect, followed by innovation, and price is the least. This indicates that customers value novel and appealing ideas more than they value low prices. Nevertheless, the study's sample size, research aim, and number of variables are all somewhat small. Consequently, it is advised that future studies broaden the scope of the study and include more factors. Practically, business practitioners should focus on developing appealing concepts, fostering innovation, and setting appropriate pricing strategies to enhance competitiveness.